The Implementation of Islamic Education in Shaping Students' Religious Behavior at Yala Rajabhat University, Southern Thailand - Fitri Amira; Asep Saepudin; Inayatillah Ridwan (PT. Anagata Sembagi Education, 2025)
This study aims to examine the implementation of Islamic education in shaping the religious behavior of students at Yala Rajabhat University, Thailand a higher education institution located within a Muslim minority community that upholds strong religious values. The research employs a qualitative descriptive approach, utilizing data collection techniques such as direct observation on campus, in-depth interviews with lecturers and students, and documentation review of religious activities. The findings indicate that the implementation of Islamic education is reflected through various programs, including memorization of hadith (tahfizhul hadits), the delivery of religious advice before classes begin, the fostering of social bonds among academic members, commemorations of Ma’al Hijrah, celebrations of the Prophet Muhammad’s birthday (Maulid Nabi), and collective Qur’anic recitations. These programs are not merely ritualistic but contribute to the formation of positive habits and reinforce students' Islamic identity in daily life. Carried out in a structured and continuous manner by the university, these efforts significantly contribute to instilling religious values that influence students’ character, ethics, and spiritual commitment.